Hepatobiliary Involvement in Neonates With COVID-19 Infection: A Previous Case Series Studies - Roya Farhadi (Mazandaran University of Medical Sciences, 2023)
Background: The most common symptoms in neonates with severe COVID-19 infection have been respiratory problems. The virus may adversely affect organs such as the liver.  Methods: Studies focusing solely on liver involvement in newborns with COVID-19 infection were searched in Pubmed, Scopus, and Google Scholar databases. Eight studies were finally reviewed. Results: Direct viral invasion (COVID-19-induced hepatitis or systemic inflammatory response) and drug-induced may contribute to liver damage in neonates. SARS-CoV-2 may be the latest spark in toxoplasmosis, other agents, rubella, cytomegalovirus, herpes infections, and fetal liver involvement may be induced by transplacental transmission.  Conclusions: Hepatic dysfunction is infrequent but important in neonates with COVID-19 infection and the mechanism of liver damage associated with COVID-19 may differ from that in adults.